ADVANTAGES OF "CENSORSHIP" AND ITS NEED TO CREATE MOVIE ("Conference on Universal Science Research 2023", 2023)
This article is devoted to the analysis of the advantages of censorship in cinema and its disadvantages. There is a list of disadvantages of lack of censorship and its impact on young people